The Effect of TNF-α Inhibitors on Nail Psoriasis and Psoriatic Arthritis—Real-World Data from Dermatology Practice - Georgios Kokolakis (MDPI AG, 2021)
Patients with psoriatic arthritis (PsA) often develop joint symptoms years after their initial diagnosis of psoriasis disease; therefore, dermatologists should test for and detect PsA early. In this study, we focused on patients with psoriasis with both nail and joint disease being treated with tumor necrosis factor-α inhibitors by dermatologists. We performed a noninterventional, prospective, multicenter, and open-label study to evaluate the effectiveness of adalimumab, etanercept, or infliximab over 24 months of continuous therapy in patients with moderate to severe plaque-type psoriasis (Pso) and PsA. Disease assessments with the Psoriasis Area and Severity Index, Nail Psoriasis Severity Index (NAPSI), joint assessment, Dermatology Life Quality Index (DLQI), and Health Assessment Questionnaire (HAQ) instruments were performed every 3 months for the first year and twice annually thereafter. The cohort included 100 patients with Pso, nail psoriasis, and PsA. A significant reduction of NAPSI was observed 3 months after therapy initiation compared with the baseline (mean ± SD, 22.9 ± 17.8 vs. 33.8 ± 21.4; p < 0.001). Similarly, the mean ± SD number of both tender and swollen joints decreased significantly within the first 3 months of treatment, from 10.8 ± 11.5 to 6.4 ± 10.3 (p < 0.001) and from 6.4 ± 9.5 to 3.1 ± 7.2 (p < 0.001), respectively. Additionally, the distal interphalangeal joint involvement improved throughout the observation time, and DLQI and HAQ scores decreased. Improvements in control of skin, nail, and joint symptoms were seen, as well as in patients’ quality of life and functionality. Dermatologists have an important role not only in PsA diagnosis but also in PsA long-term care.